Geochemistry of Gorgu Pb-Zn Mine-Waste, Malatya, Turkiye - Kalender, Leyla; Kirat, Gullu; Bolucek, Cemal; Sagiroglu, Ahmet (Tmmob Jeoloji Muhendisleri Odasi, 2009)
The study area is located at the Malatya L40-a4 section of the 1/25000 scale map 9 km southeast of Gorgu village in the Yesilyurt township, in Malatya. The Gorgu (Cafana) Pb-Zn mineralization forms in volcanic rocks (of unknown age) and in Malatya Metamorphic rocks (Permo-Carboniferous), and a great deal of mineralization take place in andesitic rocks as vein forming. The Pb-Zn mineralizations have been observed as sulphur minerals. Major minerals are galena, sphalerite, pyrite-marcasite, smithsonite (the dominant ore mineral), zincite, hydro-zincite, anglesite, cerussite and gangue minerals as represented in barite, dolomite, quartz and calcite. In this study, 12 mine waste samples and 18 soil samples were collected from within mine waste piles and around ore deposits, and the concentrations and distribution of the metals were determined. Metal concentrations in the mine wastes and soil samples range as follows: Pb 315 to > 10000 ppm (mean 6259), Zn 526 to > 10000 ppm (mean 6618), Ag 137 to 18333 ppb (mean 3711), Mn 54 to 3153 ppm (mean 829), Ba 56 to 1697 ppm (mean 546); Pb 28 to 446 ppm (mean 115); Zn 58 to 9095 ppm (mean 660); Mn 477 to 1634 ppm (mean 993); Ba 120 to 1414 ppm (mean 276); Cd 0,38 to 54 ppm (mean 4,3); Ag 25 to 2508 ppb (mean 120). Correlations of element concentrations between waste and soil show that Au, Mn, Sn, Cu, Sb, Rb and Sr values in the soil are higher than waste, due to natural weathering processes. Spearman correlation coefficients were evaluated because the data were insufficient. A high metal concentration in the soils is probably the result of natural weathering processes.
Keywords: Gorgu Pb-Zn mineralizations; geochemistry; mine waste; soil pollution